Perspectives on teachers as digital library users. Consumers, contributors, and designers - Mimi Recker (D-Lib Magazine, 2006)
"...freed of the constraints of physical space and media, digital libraries can be more adaptive and reflective of the communities they serve. They should be collaborative, allowing users to contribute knowledge to the library, either actively through annotations, reviews, and the like, or passively through their patterns of resource use. In addition, they should be contextual, expressing the expanding web of inter-relationships and layers of knowledge that extend among selected primary resources. In this manner, the core of the digital library should be an evolving information base, weaving together professional selection and the 'wisdom of crowds.'" (Lagoze, Krafft, Payette, & Jesuroga, 2005) This quote, taken from an article in a recent issue of D-Lib Magazine, paints a compelling picture of how digital libraries should evolve in ways distinct from traditional libraries. It suggests that digital libraries should exploit "Web 2.0" capabilities in order to support collaboration, contextualization, and user contributions. In short, digital libraries should implement new models of user interaction that go beyond simple (but powerful) search, which typically relies on expressive (but expensive) metadata (Sumner & Marlino, 2004).
Keywords: collaboration; enseignement